The effect of firewood combustion cookstove types on indoor air pollution and deforestation in selected rural houses of Ethiopia - Fekadu, Miftah; Molla, Moges; Hailu, Birhanu (Frontiers in Environmental Science, 2024)
Introduction Indoor air pollution occurs in a microenvironment such as residential homes, closed working places, or industries in which people spend a large part of their time. Cooking or baking food in traditional or open three-stone cookstoves by using firewood is the cause for kitchen-related smoke indoor air pollution and deforestation. Modifying traditional firewood cookstoves could reduce the emissions of indoor air pollutants. The objective of the present study was to determine the effect of firewood cookstove types on indoor air pollution, emission reduction, and deforestation in selected rural houses of Bure, Ameya, and Dalocha woredas (districts) of Ethiopia. Methods Indoor air pollutants such as carbonmonoxide (CO), carbon dioxide (CO2), sulfurdioxide (SO2), and particulate matters (PMs) were measured in three replicates for 3 min. within an average cooking time of 1 h using an automatic gas sensor. The amount of wood was separately measured by using graduated weight balance (0.1 gm). Results and discussion The cooking place was mostly the same room as the sleeping place without a separate kitchen. The improved cookstoves were installed without a chimney (smokeoutlet) and with wider spaces left for a firewood inlet. In improved Injera baking cookstoves, the mean emission of CO was 1004.80 mg/m3, 33.00 mg/m3, and 53.85 mg/m3 in Bure, Ameya, and Dalocha woredas, respectively, which were lower than the emissions from open cookstoves. The mean concentration of PM2.5 in open cookstoves in Bure, Ameya, and Dalocha woredaswas 124.50 mg/m3, 0.53 mg/m3, and 0.04 mg/m3, respectively, which are higher than the emission from improved stoves. In Bure woreda households, the CO exposure was above 26 times the permissible limit of WHO standards. Biomass consumption was positively correlated with the moisture content of wood (p < 0.05). Improved cookstoves reduced indoor air pollution by 13%–81% and carbon emission and deforestation by 20%–41% when compared with the open three-stone cookstoves. Indoor air pollutants are risks to health and cause climate change problems. Therefore, awareness should be created on the health effects of firewood smoke indoor air pollution, ventilation of cooking places, and installation of chimneys with improved cookstoves.